The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/imj.15588
|View full text |Cite
|
Sign up to set email alerts
|

Consensus guidelines for antifungal prophylaxis in haematological malignancy and haemopoietic stem cell transplantation, 2021

Abstract: Antifungal prophylaxis can reduce morbidity and mortality from invasive fungal disease (IFD). However, its use needs to be optimised and appropriately targeted to patients at highest risk to derive the most benefit. In addition to established risks for IFD, considerable recent progress in the treatment of malignancies has resulted in the development of new 'at-risk' groups. The changing epidemiology of IFD and emergence of drug resistance continue to impact choice of prophylaxis, highlighting the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 178 publications
0
62
0
Order By: Relevance
“…Among patients without COVID-19, antifungal prophylaxis is often indicated when there will be prolonged neutropenia, typically in the setting of malignancy, chemotherapy, or other immunosuppression [ 50 ]. Medication selection is often between triazole agents, amphotericin B, echinocandins, or combination therapy with voriconazole with an echinocandin, liposomal amphotericin B with an echinocandin, or amphotericin B with a triazole [ 51 ]. Posaconazole has been shown to be effective in reducing the incidence of IPA and mortality among neutropenic patients with acute myeloid leukemia and those with graft-versus-host disease after allogeneic hematopoietic stem cell transplant [ 52 , 53 ].…”
Section: Current Data On Antifungal Prophylaxismentioning
confidence: 99%
“…Among patients without COVID-19, antifungal prophylaxis is often indicated when there will be prolonged neutropenia, typically in the setting of malignancy, chemotherapy, or other immunosuppression [ 50 ]. Medication selection is often between triazole agents, amphotericin B, echinocandins, or combination therapy with voriconazole with an echinocandin, liposomal amphotericin B with an echinocandin, or amphotericin B with a triazole [ 51 ]. Posaconazole has been shown to be effective in reducing the incidence of IPA and mortality among neutropenic patients with acute myeloid leukemia and those with graft-versus-host disease after allogeneic hematopoietic stem cell transplant [ 52 , 53 ].…”
Section: Current Data On Antifungal Prophylaxismentioning
confidence: 99%
“…In the last decades, the development of new therapies, such as inhibitors of tyrosine kinase (e.g. ibrutinib) or Janus-kinase, checkpoint-inhibitors, and CAR-modified T-cells (due to the use of steroids and tocilizumab for the prevention of cytokine release syndrome), has also been associated with higher risk for IA [ 7 , 8 , 9 ]. Among solid organ transplant (SOT), lung transplant recipients have the highest risk of IA.…”
Section: Introductionmentioning
confidence: 99%
“…Antifungal prophylaxis for high-risk populations, especially those with acute myelogenous leukemia (AML) and myelodysplastic syndrome (MDS) who are undergoing chemotherapy, is reasonable and has been widely recommended as a standard strategy in clinical practice ( 6 – 9 ). Posaconazole, a second-generation triazole with a broad antifungal spectrum, has been strongly recommended in multiple foreign guidelines as the sole first-line agent with the highest level of evidence and recommendation for IFI prevention in high-risk AML or MDS patients ( 6 – 8 ). These recommendations were initially built on the basis of a pivotal randomized controlled trial (RCT), which showed a lower IFI occurrence rate and longer survival time in hematological malignancy patients receiving posaconazole than in those receiving the first-generation triazoles fluconazole or itraconazole ( 10 ).…”
Section: Introductionmentioning
confidence: 99%